Percutaneous Palliative Surgery for Femoral Neck Metastasis Using Hollow Perforated Screw Fixation and Bone Cement - Kim, Yong-il (JB JS Open Access, 2017)
BACKGROUND: We introduced a new surgical method of percutaneous hollow perforated screw (HPS) fixation with concomitant bone-cement injection for the treatment of femoral neck metastasis and evaluated its efficacy for the palliative treatment of patients with advanced cancer. METHODS: The study included 87 patients (39 men and 48 women; mean age [and standard deviation], 64.2 ± 10.2 years; mean body mass index, 24.3 ± 3.2 kg/m(2)) who underwent percutaneous HPS fixation and cementoplasty (mean cement amount, 19.8 ± 8.3 mL) for the treatment of unilateral or bilateral femoral neck metastasis (total, 95 sites). Anesthesia type, operative time, operative blood loss, pain score changes (according to a visual analog scale [VAS]), walking status, and complications were assessed. The mean duration of follow-up was 10.1 ± 10.8 months (range, 2 to 43 months). RESULTS: The majority of procedures were performed with local (3 patients) or spinal (72 patients) anesthesia (total, 75 patients; 86.2%). The mean operative time was 35.9 minutes, and the mean operative blood loss was 97.0 mL. The VAS score for pain improved significantly, from 6.8 ± 2.8 preoperatively to 2.8 ± 2.3 and 2.9 ± 2.8 at 1 and 6 weeks postoperatively (p < 0.001). At 6 weeks postoperatively, 63 (80.8%) of 78 patients were able to walk (with either normal or limping gait, a cane or crutch, or a walker). The prevalence of major local complications (cement leakage into the hip joint, fixation failure) was 10.5% (10 of 95), but major systemic complications (distant cement embolism) were not found. CONCLUSIONS: Percutaneous HPS fixation and cementoplasty for the treatment of femoral neck metastasis is a minimally invasive technique that provides effective pain relief and early stabilization. This technique seems to be useful for patients with advanced cancer for whom open surgery would be hazardous. LEVEL OF EVIDENCE: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.